DAMPAK PERCERAIAN ORANG TUA TERHADAP PRESTASI ANAK (STUDI KASUS DI KECAMATAN NANGGUNG, BOGOR) - Musa Alfadhil; Nurma Dewi; Samwil Samwil (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
The main goal of household to shape  family which sakinah, mawadah and rahmah, glad and peaceful. Husband and wife must cooperate to get this goal. Husband and Wife must give way all of conflict at their household. The problem of this research are (1) How divorce process as Sharia and rule of law? (2) How Parent Divorce Effect for Junior High School Children Performance at SLTP Nanggung district?. The goal of this research to know (1) way of divorce as sharia and rule of law? (2) impact of parent divorce for children performance at SLTP Nanggung district. (3) strategy to build children at junior high school stage sacriface parent divorce in Nanggung district. This researh is desciptive qualitative use data collection technique, interview, observation, documentation and triangulation and data analysis technic interactive model. There are data collection, data reduction, data presentation, and conclusion. Source of data from primary and secondary data. The impact of parent divorce are very complex. There are jerk of soul, lower of spirit to achieve ideal, lower of spirit to study and criminal action as children battle, use of narkoba, free sex, etc. Strategy to build children from impact of parent divorce by comprehensive religion education, formal or non formal.         Kata kunci: Perceraian Orang tua, Prestasi Belajar, Anak Usia SLTP.